Pendidikan Merdeka Belajar dalam Perspektif Filsafat Progresivisme - Adisel, Adisel; Suryati, Suryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the concept of independent learning education in the perspective of progressivism philosophy. The approach used is a qualitative approach with the method of literature or literature review (literature review/literature research). The material used as a study is books and journals that are relevant to the perspective of philosophy and the Freedom to Learn policy. The analysis process in this study includes: data reduction, verification and drawing conclusions. The results of the study show that the current education system was conceptualized by the Minister of Education and Culture referring to the concept of progressive philosophy of thought put forward by John Dewey, where the philosophical value requires: 1) the existence of independence and flexibility of educators and educational institutions in exploring maximally abilities, intelligence and the potential of students in a flexible, natural, fun and democratic way, 2) improving student character as a manifestation of social aspects in progressivism 3) there is a change in educational practice to a more advanced, quality and modern direction quickly and provide real benefits for participants educate. Conclusion. Optimizing the concept of Freedom to Learn is expected to be able to improve the quality of resources and the competitiveness of students in a globalized world. Keywords: Free Learning, Progressivism, Education.